2020
DOI: 10.1177/0956247820944823
|View full text |Cite
|
Sign up to set email alerts
|

Mapping repertoires of collective action facing the COVID-19 pandemic in informal settlements in Latin American cities

Abstract: How are civil society organizations responding to COVID-19’s impacts on informal settlements? In Latin America, civil society organizations have developed a repertoire of collective action, seeking to provide immediate and medium-term responses to the emergency. This paper aims to map these initiatives and identify strategic approaches to tackle the issues, given the strengths of those undertaking the initiative, and the scope, purpose and sphere of intervention. Using direct contact, a survey, and a virtual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…The results demonstrate that community cooperation is more effective for leveraging human capital and technology to meet victims’ needs of transportation and logistics, equipment, food and water, medicine, and other necessities. Duque Franco et al (2020) suggested that grassroots initiatives are vital in providing immediate responses to emergencies in temporary settlements, including transport, mobility, food, and water; however, the long-term deployment of materials and services in the recovery phase requires the coordination of public authorities. Odendaal (2020) discussed the co-existence of governmental and public responses in South Africa, which they suggested could be attributed to safety concerns, system and infrastructure failure, and poor well-being of the community.…”
Section: Discussion Of Policy Implicationsmentioning
confidence: 99%
“…The results demonstrate that community cooperation is more effective for leveraging human capital and technology to meet victims’ needs of transportation and logistics, equipment, food and water, medicine, and other necessities. Duque Franco et al (2020) suggested that grassroots initiatives are vital in providing immediate responses to emergencies in temporary settlements, including transport, mobility, food, and water; however, the long-term deployment of materials and services in the recovery phase requires the coordination of public authorities. Odendaal (2020) discussed the co-existence of governmental and public responses in South Africa, which they suggested could be attributed to safety concerns, system and infrastructure failure, and poor well-being of the community.…”
Section: Discussion Of Policy Implicationsmentioning
confidence: 99%
“…In the US, for instance, non-compliance with COVID-19 preventive measures were more likely to occur in areas with higher cultural emphasis on individual freedom (Bazzi et al, 2020). In addition to symbolic threats to freedom and individualistic values, other protests emerged as a consequence of threatened fairness and justice-related values (see Bartusevicius et al, 2020;Duque-Franco et al, 2020) due to the pandemic's effect as an amplifier of socioeconomic inequalities (Davidai et al, 2020). COVID-19 spread -due to its foreign origin -may also activate elements of 'ownership threat', whereby one's group rights to decide about their own country, cultural values, and local policies are felt to be taken away (Nijs et al, 2021).…”
Section: Covid-19 From a Threat-regulation Perspectivementioning
confidence: 99%
“…In such approaches communities are seen as targets of risk communication and sources of data for decisions made elsewhere, with superficial forms of consultation. In contrast, in some countries or local settings, affected communities and their organisations have played more substantive, meaningful roles in planning and reviewing responses, and have been involved in key measures for prevention, care and social protection (Bhaduri, 2020;Duque Franco et al, 2020;Scheepers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%